Measuring Road Roughness and Its Effects on User Cost and Comfort 1985
DOI: 10.1520/stp34592s
|View full text |Cite
|
Sign up to set email alerts
|

Root-Mean-Square Vertical Acceleration as a Summary Roughness Statistic

Abstract: Much has been done in recent years to relate various roughness statistics to rider comfort in terms of a serviceability index (developed by Carey and Irick). Much less has been done on correct evaluation of a true profile in terms of summary statistics for field comparison of vehicle operating costs and user comfort. Important work in this area has been done by Gillespie and Sayers at the University of Michigan, and additional work has been done by Hudson, Williamson, and McKenzie at the University of Texas. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The above results are not surprising as it has been widely known among pavement researchers that each of the above roughness indices was calculated with either a specific mathematical equation or model and is thus sensitive to roughness features of a particular frequency range (1,9). That this is so can be demonstrated by examining the coefficients of correlation between each of these roughness indices and the various wavelet subband energy terms.…”
Section: Analysis For Flexible Pavementmentioning
confidence: 65%
“…The above results are not surprising as it has been widely known among pavement researchers that each of the above roughness indices was calculated with either a specific mathematical equation or model and is thus sensitive to roughness features of a particular frequency range (1,9). That this is so can be demonstrated by examining the coefficients of correlation between each of these roughness indices and the various wavelet subband energy terms.…”
Section: Analysis For Flexible Pavementmentioning
confidence: 65%
“…On the other hand, a report by the environmental agency, UK [35] described that the rigid concrete structures such as sea defences, retaining walls and sea walls may cost as high as 750 US$/m 2 to 7500 US$/m 2 (543 to 5467 £/m 2 ). The flexible erosion control systems do not exhibit strength characteristics, but it is the most used product due to their low cost, as mentioned in Table 2.…”
Section: Cost and Construction-efficiencymentioning
confidence: 99%
“…Researchers have long conducted studies to determine correlations between perceptions of roughness and the objective measures of roughness from various devices. For example, researchers found that the rootmean-square vertical acceleration (RMSVA) obtained from a Mays Ride Meter, which is the difference between adjacent slope measurements, was useful in equipment calibration, but unreliable as a predictor of panel ratings (Hudson, et al 1983). Generally, the lack of agreement between various roughness measuring devices circumvented the definition of a uniformly accepted single-index characterization of roughness until the World Bank defined the IRI in 1982 as a standard, objective measure of roughness (Gillespie, Sayers and Queiroz 1986).…”
Section: Perceptions Of Roughnessmentioning
confidence: 99%